Selective conversion of polyenes to monoenes by RuCl 3-catalyzed transfer hydrogenation: The case of cashew nutshell liquid - Perdriau, Sebastien; Harder, Sjoerd; Heeres, Hero J.; De Vries, Johannes G. (Chemsuschem, 2012)
Cardanol, a constituent of cashew nutshell liquid (CNSL), was subjected to transfer hydrogenation catalyzed by RuCl using isopropanol as a reductant. The side chain of cardanol, which is a mixture of a triene, a diene, and a monoene, was selectively reduced to the monoene. Surprisingly, it is the C8-C9 double bond that is retained with high selectivity. A similar transfer hydrogenation of linoleic acid derivatives succeeded only if the substrate contained an aromatic ring, such as a benzyl ester. TEM and a negative mercury test showed that the catalyst was homogeneous. By using ESI-MS, ruthenium complexes were identified that contained one, two, or even three molecules of substrate, most likely as allyl complexes. The interaction between ruthenium and the aromatic ring determines selectivity in the hydrogenation reaction. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.